2019
DOI: 10.1097/hp.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Kinetic Parameters for 123I Uptake by the Thyroid, Thyroid Weights, and Thyroid Volumes in Present-day Healthy Japanese Volunteers

Abstract: The purpose of this study was to evaluate the kinetic parameters that determine the uptake rate of radioiodide in the thyroid over 24 h after administration and to estimate thyroid volumes/masses of present-day Japanese. Methods: We determined the thyroid uptake rate of 123I in healthy male Japanese after oral administration (4.5–8.0 MBq) without iodine restriction. Masses of thyroid glands were collected in 2012–2016 during autopsies of 7,651 male and 3,331 female subjects. Volumes of thyroid glands were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ WSPEEDI_2019DB, which was improved by referring to hourly measured 137 Cs concentrations in air at multiple SPM stations 26 . In addition, two factors that influence TEDs were incorporated into the present dose estimation: a decontamination factor for sheltering and a correction factor for dose coefficient to reflect the lower thyroid iodine uptake rate in Japanese 18,24 . By these procedures, we estimated 131 I-TEDs as realistically as possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…www.nature.com/scientificreports www.nature.com/scientificreports/ WSPEEDI_2019DB, which was improved by referring to hourly measured 137 Cs concentrations in air at multiple SPM stations 26 . In addition, two factors that influence TEDs were incorporated into the present dose estimation: a decontamination factor for sheltering and a correction factor for dose coefficient to reflect the lower thyroid iodine uptake rate in Japanese 18,24 . By these procedures, we estimated 131 I-TEDs as realistically as possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, such individual information was not available or was obtained only in exceptional cases. Instead of assessing individual dietary habits, we adopted the distribution of iodine uptake rate reported by Kudo, who experimentally assessed the rate among normal subjects without iodine restriction 18 . Sixth, SF, a correction factor for short-lived radionuclides, might vary from place to place on 12 March, as P1 was a mixture of two plumes released by venting at 14:30 and by a hydrogen explosion at 15:36, and venting might deplete low volatile 132 Te in the plume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of the public's exposure in the FDNPP accident have addressed the relatively low thyroid iodine uptake (TIU) (Hosoda et al 2013;Kim et al 2016c;Ohba et al 2020). It was also reported that the average TIU factors in Japanese subjects were mostly in the range of 0.15-0.20 (Yoshizawa and Kusama 1976), which was also found to be true in a very recent study (Kudo et al 2020). The relatively low TIU in the Japanese is due to their diet (in which stable iodine is abundant) and will reduce the TED coefficients that were calculated assuming the TIU factor of 0.3; the corresponding coefficients for the Japanese are thought to be decreased by the ratio of the Japanese TIU factor to 0.3.…”
Section: Discussionmentioning
confidence: 79%
“…Once Kudo et al . [ 39 ] demonstrated the distribution of thyroid weight, iodine uptake rate and other bio-kinetic parameters in Japanese people, it became possible to propose a correction factor for the 131 I-dose coefficient. Seventh, in contrast to UNSCEAR’s supposition that Fukushima residents consumed contaminated vegetables and other foodstuffs grown in Fukushima Prefecture, Hirakawa et al .…”
Section: Estimated Thyroid Doses After the Fdnps Accident—estimation After 2016mentioning
confidence: 99%